Toxocara canis eggs determination in Duitama (Colombia) three public parks soil - Guarín-Patarroyo, Camilo Ernesto; Serrato, Marly Julieth; Sánchez-Cuervo, Fabián Rodrigo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Toxocara canis is an Ascarideo nematode, common in the small intestine of dogs, which become infected through transplacental migration by galactogen way, or embryonated eggs ingestion. It also infects humans, mainly affects children under five years old, producing human toxocariasis, and classified as a neglected zoonosis. Infestation is especially spread by ingestion of contaminated soil and vegetables without adaquated health management, and causing illiness such as Migratory Syndrome Visceral Larva, plus dermal and ocular toxocariasis. The aim of the study was to determine by the Sloss technique the presence of Toxocara canis eggs in Duitama three public parks soils, besides to identify the Toxocara canis transmission mechanisms in the population that goes to these parks. For that purpose, were collected 76 samples from the ground, 10 cm long, by 10 cm wide, and 3 cm depth, then stored in sealed plastic bags, for a later study at the laboratory. The results indicate that parasite eggs were found in 34.7% of the samples collected, ponting a risk level to the population. According to Variables pH, humidity and strata, no association between them and the identification ofthe egg was obtained. Nevertheless, the presence of T. canis in the parks indicates that the population of the city of Duitama is exposed to the serious potential risk of acquiring the parasite.